Letting the walls of the city speak:: The route of a sociological research project on Lisbon’s street art1 - Sequeira, Ágata Dourado (Street Art & Urban Creativity, 2015)
This article sets out to show how a sociological research project on the production of street art in Lisbon was built, from the construction of an object of research to the development of a methodological approach that enabled the collection of a diverse set of expressive data. The notion of ‘route’ serves not only as a valuable instrument of research in the first stages of an investigation in urban sociology, but also as a powerful visual depiction of the development of a specific methodology and the set of techniques adopted. The diverse set of interrogations about the object that stem from these incursions, as well as the specific urban context at hand, allowed the researcher to conceptualize street art as a component of contemporary urban space and as a visual means to reveal social dynamics between the several actors involved in its production, and the city itself. Therefore, in this paper it is briefly shown how this object is theoretically framed, namely in what concerns the street artists and the way they build an artistic path and attribute meaning to the act of intervening artistically in the streets of the city, and how this connects with the worlds of contemporary art and the several contexts of production of street art; the contexts in which street art is currently created in Lisbon, from individual initiatives to the actions of associations or collectives, and the municipality; and the way in which the city, through its institutional powers, can instrumentalize street art as a way of creating ‘images of the city’, and how this can be explored in terms of tourism and the marketing of cities, and the conflict or opportunities that these processes reveal for the actors involved.